PENGARUH PERSEPSI TENTANG CHARACTER ARTIFICIAL INTELLIGENCE TERHADAP KETERAMPILAN SOSIAL INDIVIDU DEWASA MUDA - Kyara Nathashia; Meike Kurniawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technology continues to evolve rapidly, with Artificial Intelligence (AI) becoming increasingly utilized across various sectors. Currently, AI technology has permeated the sphere of human social interaction, functioning as companions or partners, typically manifested through chatbot-based conversational applications. The progression of time, culture, and technology presents new challenges for the development of social skills in young adults. Given the prevalence of AI-based chatbot applications, this study aims to explore the role of young adults' perceptions of Character Artificial Intelligence on their social skills. This research utilized a quantitative method employing simple regression data analysis techniques. The findings indicate that young adults' perceptions of Character Artificial Intelligence contribute positively and significantly, accounting for 9.9% of the variance in social skills.